Model-based requirements engineering - Holt, Jon (Professional applications of computing series ;, 2012)
This book provides a hands-on introduction to model-based requirementsengineering and management by describing a set of views that form the basisfor the approach. These views take into account each individual requirement interms of its description, but then also provide each requirement with meaning byputting it into the correct 'context'. A requirement that has been put into a contextis known as a 'use case' and may be based upon either stakeholders or levelsof hierarchy in a system. Each use case must then be analysed and validated bydefining a combination of scenarios and formal mathematica.